Peoples' perspectives of community forestry : view from south east Pahang peat swamp forest, Malaysia - Muhammad Adha bin Mohd Shaleh (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, Internationai Islamic University Malaysia, 2015)
This research aims to explore respondents' perspectives on forest conservation. Equally important to the focus of the research is to explore the key condition that helps account to the successful establishment of community forestry in the conservation area of South East Pahang Peat Swamp Forest (SEPPSF). It is anticipated that the knowledge generated from this research would afford new insights about forest management. It hopes that knowledge generated from this research would also be a groundswell support to pilot community forestry in the highly bio-diverse ecosystem of SEPPSF. Further it hopes that discussions and recommendations generated from the research would be a catalyst to forestry planners to initiate transition in forest management, from central state control to community based forest management. This study employed qualitative case study methodology to illustrate respondents' perspectives on forest conservation and the key condition under investigation. Respondents of this study included a mixture of purposefully selected 15 people varying from local communities (Jakun) who used to live in and around South East Pahang Peat Swamp Forest, scientists who research forest policies and social scientists who work on community rights in forest management. The research was based on two research questions: 1) What perspectives do people hold with regard to forest conservation, and 2) What is the key condition people envision as relevant that helps account to the establishment of community forestry in forest conservation area. After careful analysis of the current forest policy mainstream in SEPPSF, the mainstream thinking does not have a structure to springboard a community centred forest conservation project. The ensuing situation grabs the attention of respondents in the research, and through an extensive discussion with the respondents, this research agreed on three things. First, for community forestry to take shape in SEPPSF, the authority must recognize local communities' right in forest management. Second, for community forestry to carry on in the longer run, local communities have to be part of forest conservation activities that benefit them in long term. Third, prior to the trial of community centred conservation project, a study on peoples' perspectives towards forest conservation precedes other priorities. People perspectives are crucial in terms of deciding the suitable conservation projects that are congruent to local environmental condition.